2020
DOI: 10.1039/c9ra09594b
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gut microbiota on the rheological characterization of soy hull polysaccharide and mucin interactions

Abstract: SSHP increased the viscoelasticity of the interfacial film and reduced the interfacial tension at the air–water interface by interacting with mucin. SSHP increased the ratio of Proteobacteria and Firmicutes and promoted the growth of probiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Intestinal flora, as an indispensable component of feces, plays an important role in TAG metabolism. Previous studies have indicated that a wide variety of microbes reside in the gastrointestinal tract of healthy individuals . These bacteria comprise the gut microbiota, which is a large and complex ecosystem, with more than 400 species of bacteria in the human colon. , Many studies have shown that the intestinal microbiota is an important part of the intestinal microecosystem and plays a crucial role in physiological functions and processes, such as nutrient absorption, growth, development, and biological barriers in the body .…”
Section: Resultsmentioning
confidence: 99%
“…Intestinal flora, as an indispensable component of feces, plays an important role in TAG metabolism. Previous studies have indicated that a wide variety of microbes reside in the gastrointestinal tract of healthy individuals . These bacteria comprise the gut microbiota, which is a large and complex ecosystem, with more than 400 species of bacteria in the human colon. , Many studies have shown that the intestinal microbiota is an important part of the intestinal microecosystem and plays a crucial role in physiological functions and processes, such as nutrient absorption, growth, development, and biological barriers in the body .…”
Section: Resultsmentioning
confidence: 99%
“…There is also the presence of pectin (4.2%) and protein (9.4%) 1,2 . It has been confirmed that soy hull polysaccharide (SHP) has excellent biological activity and a new type of natural dietary fiber energy 3 . Recently, Han et al 4 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It has been confirmed that soy hull polysaccharide (SHP) has excellent biological activity and a new type of natural dietary fiber energy. 3 Recently, Han et al 4 indicated that SHP has the potential to be developed as a new functional food contributing to the alleviation of liver damage. Yet at the same time, since SHP is rich in hydroxyl groups and has a small amount of protein, our previous studies demonstrated that it had good emulsification, thickening, and gelation properties.…”
Section: Introductionmentioning
confidence: 99%
“…1 The interaction between polysaccharides fermented by intestinal microbes and IM has received extensive attention. 2 IM—a glycoprotein network that exists on the membrane surface of intestinal epithelial cells—consists mainly of water (95% w/w) and mucin (about 5% w/v). 3 Mucin is a high molecular weight glycoprotein formed and released by goblet cells, which consume glutamine and a large number of other amino acids.…”
Section: Introductionmentioning
confidence: 99%